Compósitos biodegradáveis a partir de poli(succinato de butileno) e resíduos de cacau para manufatura aditiva - Araújo, Robson Pinto (2023)
Additive manufacturing (AM) has developed a lot in recent years, however, the diversity of materials available for application in its different techniques is still limited and few biodegradable materials are available for the Fused Filament Fabrication (FFF) process. Poly(Butylene Succinate) (PBS) is a biodegradable polymer that can be obtained from raw materials of fossil origin and/or from renewable sources. PBS presents high crystallinity and low resistance in the molten state, characteristics that must be controlled so that the material can be used for application in FFF processes. Such properties can be changed through the insertion of natural fillers, in the form of particles, thus developing low-cost composites, with improved characteristics for biodegradation and environmentally friendly. Therefore, this project aimed to develop filaments from the PBS matrix and cocoa bean shells (CBS) from agro-industrial waste. The filaments were produced by extrusion and their properties were evaluated in terms of rheological and thermal characteristics. The composites were formed through injection molding and additive manufacturing. The mechanical properties were evaluated under tensile strength and the disintegration process of the printed and injected parts was evaluated with soil deposition. The results showed that the incorporation of CBS altered the rheological behavior of the PBS matrix in order to favor the filament production processes and 3D printing. However, the printed specimens showed inferior mechanical properties compared to the properties of injection molded specimens. The incorporation of CBS fractions resulted in an increase in the disintegration rate for printed and injected parts.